A comparative analysis of the interrelation between the evolution in the structure of Armenian churches of the 4th-14th centuries and the three-layer “midis” masonry - Azatyan, Karen; Azatyan, Ruben; Manukian, Anzhelika; Melikyan, Mane (Budownictwo i Architektura / Civil and Architectural Engineering, 2023)
The article touches upon the interrelations between the structural elements and the building structure in architecture. The aim of the work is to generalize the peculiarities of “midis” masonry formation and to reveal its influence in the evolution process of the structure of Armenian medieval churches by a comparative analysis of different characteristics. In the work: the development of three-layer “midis” masonry was systematized, the phenomenon of shell structure and spatial integrity in the churches of the 4th-14th centuries was highlighted, the tendencies of evolution of the masonry monolithic nature and church structure integrity were revealed by a comparative analysis of volumetric and planning characteristics of different churches. The results allowed to formulate a certain sequence of interactions in different characteristics, which confirmed the relationship between the evolution of the masonry and the structure of the churches: the evolution of “midis” masonry led to the structural monolithic nature of the walls and the forms derived from it, which in turn led to the integrity of the stone building structure. The results can be useful in further research covering structural-compositional interrelations, including both heritage and modern architecture studies.